الإعجاز في وسطية واعتدال المنهج الإسلامي - أبو سخل، عامر إسماعيل سيد (الجامعة الاسلامية بغزة, 2016)
تدور فكرة البحث عن مفهوم الإسلام (للوسطية)، خاصة في هذا الوقت الذي أصبح فيه كثير من الناس من يثبت فكر التشدد والغلو، وإظهار الإسلام بمظهر العنف، وأن الحوار لا يكون إلا بالسيف، فيمارس العنف والإجرام باسم الدين، فأصبح العالم ينظر (للإسلام) على أنه قتل وإجرام واعتداء على حقوق الآخرين؛ ومن الناس من يريد أن يثبت فكر التساهل والتهاون ويظهر الإسلام بمظهر الضعف، إما لضعف في ذاته وإما لإرضاء الآخرين؛ لذلك جاء هذا البحث؛ ليثبت أن الإسلام دين سماحة ووسطية لا تفريط ولا إفراط. وقد ناقش البحث هذه الأفكار وبيّن (سماحة الإسلام ووسطيته) في التعامل معها. وقد تناول هذا البحث تعريف (الوسطية) لغة واصطلاحاً، والوسطية في زمن النبي (صلى الله عليه وسلم) والوسطية في معاملة المخالفين، والوسطية في معاملة الأسرى والمحاربين، وصلاحية المنهج الإسلامي واستمراره في وسطيته. The idea of research on the concept of Islam of moderation, especially at this time when a lot of people to prove the thought of militancy and extremism and to show Islam appearance of violence, and that dialogue is not only the sword, Fimars violence and criminality name of religion, became the world looks to Islam as a killing and criminality and aggression the rights of others; some people who wants to prove the thought of leniency and tolerance of Islam and shows the appearance of weakness, either to weakness in itself or to please others; indeed, this research would in order to confirm that Islam is a religion of tolerance and moderation do not overcook or overeating . Find these ideas have been discussed and the tolerance of Islam and moderation in dealing with it. This research has dealt with the language of moderation and idiomatically, and moderation is defined in the time of Prophet (and moderation in the treatment of offenders, and moderation in the treatment of prisoners of war and veterans, and the validity of the Islamic approach and continuity in Stith.
Keywords: الإسلام -- المنهج الإسلامي -- الوسطية